1994
DOI: 10.1111/j.1438-8677.1994.tb00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of Phytoparasitic Fungi Introduced to Germany and Adjacent Countries

Abstract: A chronologically arranged list of 59 taxa of phytoparasitic micromycetes, introduced to Germany after 1750, is presented. Another list enumerates 15 fungal taxa which have been introduced to other parts of Europe but may be expected in Germany, too. Most of the enumerated newcomers are members of the orders Pucciniales and Erysiphales. The new terms archaeomycete, neomycete, and ephemeromycete are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 8 publications
0
27
0
2
Order By: Relevance
“…The vast majority of these species may be short lived or emphemeromycetes (Kreisel and Scholler 1994), i.e., species that disappear a short time after introduction even if potential host plants are abundant. Our studies have shown that for microcyclic rust fungi both host and fungal parasite must fulfill certain conditions to allow the fungus to become established and spread successfully over long distances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of these species may be short lived or emphemeromycetes (Kreisel and Scholler 1994), i.e., species that disappear a short time after introduction even if potential host plants are abundant. Our studies have shown that for microcyclic rust fungi both host and fungal parasite must fulfill certain conditions to allow the fungus to become established and spread successfully over long distances.…”
Section: Resultsmentioning
confidence: 99%
“…Introduced plant parasites and established alien fungi (named neomycetes by Kreisel and Scholler 1994), however, may cause severe damage and even mortality, especially on non-resistant host individuals such as genetically uniform monocultures of forest trees, crops, and ornamental plants. The introduction, spread, and epidemiology of some of these economically important rust species are well documented, e.g., the white pine blister rust Cronartium ribicola J. C. Fisch.…”
Section: Introductionmentioning
confidence: 99%
“…A native of eastern Asia (Hiratsuka 1927), this invasive parasite was first reported in the Baltics in the mid-1990s, where it arrived presumably through the trade in nursery plants (Põldmaa 1997;Hantula & Scholler 2006;Hantula et al 2009). In the last twenty years it has spread epidemically across a number of countries along a northesouth axis roughly running from latitude 60 N (Finland) to latitude 38 N (Turkey), parasitising a number of the alder species (Alnus incana Moench., Alnus cordata Loisel, Alnus glutinosa Gaertn., Alnus orientalis Decne., and Alnus viridis D.C.) it encountered in its fairly rapid descent southwards (Kreisel & Scholler 1994;Pią tek et al 2001;Szabo 2002;Rigler-Hager et al 2003;Sert & S€ umbul 2005). The fungus has also recently been reported on grey alder (A. incana) in the eastern sector of the Italian Alps (Lagorai mountain range, Trentino AltoAdige region) (Moricca & Maresi 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Its northern limit has now reached 68'h parallel in Finland. The spread appears irreversable and the species is a typical neomycete (Kreisel & Scholler 1994) in Europe. Eriksson (1992), Gja:rum (1994), Kreisel & Scholler ( 1994 ), Karis ( 1995), Gelyuta (1997), Tikhomirova & Tobias (1999).…”
mentioning
confidence: 99%
“…The spread appears irreversable and the species is a typical neomycete (Kreisel & Scholler 1994) in Europe. Eriksson (1992), Gja:rum (1994), Kreisel & Scholler ( 1994 ), Karis ( 1995), Gelyuta (1997), Tikhomirova & Tobias (1999). As summarized by Scholler (1994a), the species was first discovered in Europe in 1975.…”
mentioning
confidence: 99%